MODEL PEMBELAJARAN BERBASIS PROYEK, KREATIVITAS DAN HASIL BELAJAR MAHASISWA - Rati, Ni Wayan; Kusmaryatni, Nyoman; Rediani, Nyoman (Lembaga Penelitian dan Pengabdian kepada Masyarakat, 2017)
This study aims to examine the influence of project-based learning model for the creativity and the results of student learning partially and simultaneously, (2) to test the effect of project-based learning model to student results. This quasi-experimental research design was post-test only control group design. The study population was PGSD Undiksha VI semester student academic year 2015 as many as 175 people consisting of 5 classes. A sample of 2 (two) classes, each consisting of 63 people was obtained by random sampling group. The independent variable was the learning model that consists of two dimensions, namely project-based learning and conventional learning, while the dependent variable is the creativity and learning outcomes. Data were collected by questionnaire and tests. Data were analyzed by statistical infrensial. The hypothesis was tested by MANOVA using SPSS 16.0 for Windows. Conclusion The results of the study are: (1) There is a positive influence on project-based learning model for the creativity of the student; (2) There is a positive influence on project-based learning model for learning outcomes Elementary Science Education students; and (3) There is a positive influence on project-based learning model for learning outcomes IPA Education Elementary students simultaneously.